The Nature of Illusions: A New Synthesis Based on Verifiability - Tyler, Christopher W. (Frontiers in Human Neuroscience, 2022)
This overview discusses the nature of perceptual illusions with particular reference to the theory that illusions represent the operation of a sensory code for which there is no meaningful ground truth against which the illusory percepts can be compared, and therefore there are no illusions as such. This view corresponds to the Bayesian theory that ‘illusions’ reflect unusual aspects of the core strategies of adapting to the natural world, again implying that illusions are simply an information processing characteristic. Instead, it is argued that a more meaningful approach to the field that we call illusions is the Gregorian approach of comparing the illusory percept with the ground truth that is directly verifiable by the observer in the situation (as opposed to the authority of other experts). This concept of direct verifiability not only provides an operational definition of ‘illusion’. It also makes their interactive observation more interesting and informative. A range of illusions that illustrate the differences between these philosophical viewpoints is considered in detail.